1959
DOI: 10.1126/science.129.3364.1678.a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diisopropylfluorophosphate on Sulfhydryl Proteases

Abstract: Diisopropylfluorophosphate inhibited all the sulfhydryl proteases studied in our tests. This inhibition was most pronounced at p H 6.0. By first blocking the sulfhydryl group with p -chloromercuribenzoate, inhibition could be prevented. Neither cysteine nor choline gave appreciable reactivation of diisopropylfluorophosphate-inhibited bromelain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1960
1960
1969
1969

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Even in the absence of activator, DFP preparation D was found to give no inhibition (Table III). In addition, the present study has also reconfirmed the results of other investigators that some commercial preparations of DFP have inhibitory effects on plant proteinases when they are activated with cyanide (Masuda, 1959;Heinicke and Mori, 1959;Ota et al, 1961; Ebata and Yasunobu, 1963). Preparation C used in the present study gave a marked inhibition of stem bromelain, papain, and ficin in the presence of cyanide.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Even in the absence of activator, DFP preparation D was found to give no inhibition (Table III). In addition, the present study has also reconfirmed the results of other investigators that some commercial preparations of DFP have inhibitory effects on plant proteinases when they are activated with cyanide (Masuda, 1959;Heinicke and Mori, 1959;Ota et al, 1961; Ebata and Yasunobu, 1963). Preparation C used in the present study gave a marked inhibition of stem bromelain, papain, and ficin in the presence of cyanide.…”
Section: Discussionsupporting
confidence: 88%
“…The reconfirmation was necessary particularly in view of the results reported by other investigators that were at variance with ours. For example, Heinicke and Mori (1959) suggested that DFP is a specific inhibitor of SH proteinases; Ota et al ( 1961) found an inhibitory effect on bromelain; Masuda (1959) and Ebata and Yasunobu (1963) isolated inactive, phosphorus-containing papain and chymopapain, respectively, after incubating the enzymes with DFP in the absence of cysteine. The conclusion we have drawn from the results of the earlier and the present experiments is that DFP per se has no inhibitory effect on stem bromelain, while impurities associated with some DFP preparations may cause an inhibition by irreversibly attacking the essential SH group of the enzyme.…”
mentioning
confidence: 99%
“…Quite coincidentally, the inhibition of ficin by the impurity also increases as the pH is raised. Those who have reported SH enzymes to be inhibited by DFP have also noted this inhibition to be pH dependent (Heinicke and Mori, 1959;Ebata and Yasunobu, 1963). It is not surprising therefore that phosphorylation and inactivation have been assumed to bear a cause-andeffect relationship to each other, an assumption which appeared to be supported by the isolation of crystalline phosphorylated derivatives of DFP-inhibited papain (Masuda, 1959) and chymopapain (Ebata and Yasunobu, 1963).…”
Section: Discussionmentioning
confidence: 94%
“…The parallelism between the stoichiometry of the DFP reaction (equation 68) and the enzyme inactivation, and also the ability of substrates to protect against inhibition by DFP, (C8H,0)2P0F + EH -> E-PO(OC3H7)2 + HF (68) indicate strongly that phosphorylation occurs at the active site. Chymotrypsin, trypsin, papain, acetylcholinesterase, and phosphoglucomutase among others are subject to inhibition by DFP (204,237). When DFP-chymotrypsin is degraded by acid hydrolysis, serine phosphate is obtained (335).…”
Section: Enzymatic Catalysismentioning
confidence: 99%